2013
DOI: 10.1038/jid.2013.203
|View full text |Cite
|
Sign up to set email alerts
|

UVB Induces HIF-1α-Dependent TSLP Expression via the JNK and ERK Pathways

Abstract: Thymic stromal lymphopoietin (TSLP) may have a key role in the initiation and maintenance of allergic inflammatory diseases, including atopic dermatitis. The present study revealed that UVB radiation exposure could induce TSLP expression in human keratinocytes and a human skin equivalent model. In addition, we investigated the regulatory mechanism of UVB-induced TSLP expression in keratinocytes. TSLP expression was upregulated by transfection with pcDNA3-hypoxia-inducible factor (HIF)-1α (P402A and P564A), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…Recent studies have revealed that TSLP expression is induced by TNF-a, synthetic double-stranded RNA poly (I:C), FSL-1, flagellin, kallikrein 5, and UVB in epidermal keratinocytes [6,21,31,32]. In AD, TNF-a is released by infiltrating mast cells, T-helper lymphocytes and epidermal keratinocytes [33].…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have revealed that TSLP expression is induced by TNF-a, synthetic double-stranded RNA poly (I:C), FSL-1, flagellin, kallikrein 5, and UVB in epidermal keratinocytes [6,21,31,32]. In AD, TNF-a is released by infiltrating mast cells, T-helper lymphocytes and epidermal keratinocytes [33].…”
Section: Discussionmentioning
confidence: 97%
“…17 IECs release TSLP that conditions mucosal DCs to noninflammatory tolerogenic DCs. Jang et al 49 demonstrated that the expression of TSLP in keratinocytes is HIF-1a dependent. We were unable to detect differences in the expression of TSLP in colon tissue probably because IECs in our model express active HIF-1a.…”
Section: Hif Plays a Crucial Role In The Regulation Of Many Immune Cementioning
confidence: 98%
“…3D). To verify the exact role of HIF-1␣ in TREM-1 expression, we used pcDNA3-HIF-1␣, which stably expresses HIF-1␣ protein by amino acid replacement on the hydroxylation site (P402A and P564A) [15]. The expression of HIF-1␣ was increased by pcDNA3-HIF-1␣ transfection at the mRNA and protein levels in PMA-differentiated U937 cells (Fig.…”
Section: Mechanism Of Hif-1˛ and Hif-2˛ Upregulation By 125(oh) 2 Dmentioning
confidence: 98%
“…pcDNA3-HIF-1␣ was generated, as previously described [15]. PMA-differentiated U937 cells were transfected with either pcDNA3 empty vector or pcDNA3-HIF-1 using Lipofectamine (Invitrogen, Carlsbad, CA) according to the manufacturer's instructions.…”
Section: Hif-1˛ Expression Construct and Transfectionmentioning
confidence: 99%